Research on Security Issues of Artificial Intelligence in Smart IoT and Electrical Automation - Shangpeng Li (Innovation in Science and Technology, 2024)
This paper explores the application of artificial intelligence (AI) in smart IoT and electrical automation, along with the security challenges it brings. It outlines the important roles of smart IoT and electrical automation, and the opportunities and challenges that AI presents within them. The paper analyzes potential data security, algorithmic security, and system security issues that may arise from AI and proposes corresponding countermeasures. Through case studies, it demonstrates practical effectiveness and concludes by emphasizing the practical significance of researching security issues in this field and future prospects.